Optimal Scanning Pattern for Initial Free-Space Optical-Link Alignment - Skryja, Petr; Barcík, Peter (MDPI, 2024)
Since free-space optical links (especially fully photonic ones) are very challenging to accurately align; scanning algorithms are used for the initial search and alignment of the transceivers. The initial alignment aims to intercept the optical beam so that it hits a position-sensitive detector. However, this operation can be very time-consuming (depending on the system parameters, such as transceiver parameters, distance between transceivers, divergence of the transmitter, angle of view of the receiver, etc.). A spiral scan is used as the most widespread pattern for scanning. This article examines the effects of system parameters (e.g., global navigation satellite systems and compass accuracy) on the angular area of uncertainty that must be scanned to find the optical beam. Furthermore, several types of spiral pattern are compared depending on the time of the scan execution and the required number of points for scanning the given uncertainty area. The cut hexagonal spiral scan achieved the best results as it required 18.1% less time than the common spiral scan for the presented transceiver.

Since free-space optical links (especially fully photonic ones) are very challenging to accurately align; scanning algorithms are used for the initial search and alignment of the transceivers. The initial alignment aims to intercept the optical beam so that it hits a position-sensitive detector. However, this operation can be very time-consuming (depending on the system parameters, such as transceiver parameters, distance between transceivers, divergence of the transmitter, angle of view of the receiver, etc.). A spiral scan is used as the most widespread pattern for scanning. This article examines the effects of system parameters (e.g., global navigation satellite systems and compass accuracy) on the angular area of uncertainty that must be scanned to find the optical beam. Furthermore, several types of spiral pattern are compared depending on the time of the scan execution and the required number of points for scanning the given uncertainty area. The cut hexagonal spiral scan achieved the best results as it required 18.1% less time than the common spiral scan for the presented transceiver.
Optimal Scanning Pattern for Initial Free-Space Optical-Link Alignment
Keywords: FSO; spiral scan; spiral patterns; alignment; angular area of uncertainty; FSO; spiral scan; spiral patterns; alignment; angular area of uncertainty